Generating Community through Interpersonal Relations and Digital Media: The Experience of Italian Parishes. Quantitative Research - First Stage Results - Boccacin, Lucia; Lombi, Linda (Italian Sociological Review, 2021)
This paper has two cognitive objectives: to illustrate the contribution of Italian parishes to the development of interpersonal and associative social relationships capable of building community environments, and to improve understanding of the role played by community technology in shaping these relationships. The above were investigated using relative quantitative information culled from an online questionnaire from 420 Italian church parishes. An analysis of the data revealed the particular contribution of Italian parishes in favouring the construction of a community at both the local and symbolic levels, communities where interpersonal and digital relationships play a crucial role even if via different modes and styles.